Pidotimod – Current Role and Evidence - Yash Sanjay Kedia; Pranav Ish; Vidushi Rathi (Journal of Advanced Lung Health)
Recurrent respiratory infections (RRIs) are common in the pediatric age group and in patients with chronic respiratory disorders, leading to frequent hospitalization and poorer quality of life. Studies have shown that an immature immune system in childhood can predispose to RRIs, leading to adult life. Immunomodulators are drugs which modulate the immune system of the host to increase resistance against various infections. They interact with specific receptors and cellular components of innate and adaptive response to modulate the immune response. Pidotimod (PDT) is one such immunomodulator which has shown emerging evidence in the past 2 decades, to reduce the recurrence of lower respiratory tract infections and help in faster recovery from the same. This review highlights the evidence behind the potential role of PDT in the prevention and management of RRIs.